Program Pengabdian Masyarakat Berbasis Masjid Sebagai Mediator Pembangunan Sektor Keagamaan di Desa Talang Empat - Panca Oktoberi; Sukran Zahero; Atika Mahdia Pratiwi; Firma Wati; Helvina Dia Nengsi; Ledia Seftiani; Meike Puspita Yulia Nindri; Monika Suseria; Noni Pangestu; Rendi Sugito; Yuda Andriawan (MENYALA: Jurnal Pengabdian Masyarakat, 2024)
This community service program focuses on leveraging the mosque as a central hub for sector development in Desa Talang Empat, Kecamatan Karang Tinggi, Kabupaten Bengkulu Tengah. The main issues addressed include inadequate educational facilities, poor health awareness, and insufficient community engagement in social and environmental activities. The program aims to enhance religious engagement, improve social and health conditions, and advance educational and agricultural practices through a series of integrated activities. The approach involved conducting religious teaching, social clean-up initiatives, health exercises, educational programs, and agricultural development. Methodologically, the program utilized descriptive techniques to assess the impact of these activities. Results indicated significant improvements in community involvement and the overall quality of life. Religious activities increased participation and cohesion, social initiatives improved environmental cleanliness, health programs raised awareness and participation in fitness, educational efforts enhanced learning opportunities, and agricultural projects boosted local farming practices. This integrated approach demonstrated the mosque's potential as a catalyst for comprehensive community development.